1990
DOI: 10.1111/j.1365-2885.1990.tb00793.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of fenbendazole in dogs

Abstract: Fenbendazole was administered to dogs at a dose rate of 20 mg/kg body weight on a single occasion in gelatin capsules, on 5 consecutive days in feed, and on a single occasion as an alginate suspension. It was also administered at a dose rate of 100 mg/kg body weight on a single occasion in feed. Following single administration of 20 mg/kg fenbendazole mean maximum concentrations (Cmax) of the parent drug and its known active sulphoxide metabolite were 0.42 +/- 0.05 and 0.31 +/- 0.05 microgram/ml, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…All dogs were treated with fenbendazole or moxidectin and prednisolone and additional symptomatic medications as deemed necessary by the clinician in charge; 1 dog treated with fenbendazole (50 mg/kg) 6 hours before ROTEM analysis was included in the study because fenbendazole is not expected to have a clinically relevant anthelmintic effect within 6 h …”
Section: Resultsmentioning
confidence: 90%
“…All dogs were treated with fenbendazole or moxidectin and prednisolone and additional symptomatic medications as deemed necessary by the clinician in charge; 1 dog treated with fenbendazole (50 mg/kg) 6 hours before ROTEM analysis was included in the study because fenbendazole is not expected to have a clinically relevant anthelmintic effect within 6 h …”
Section: Resultsmentioning
confidence: 90%
“…As we mentioned above, ABZ is barely absorbed from the gastrointestinal tract since it is a poorly watersoluble drug. It was demonstrated that for monogastric species, an increment in the dose is not correlated to an increment in the AUC (McKellar et al, 1990). Moreover we demonstrated that concentrations of ABZ as low as 0.5 mg/kg exert a deleterious effect on hydatid cysts on the murine model of cystic echinococcosis (Ceballos et al, 2008).…”
Section: Discussionmentioning
confidence: 91%
“…This observation could explain the lack of efficacy of MBZ against lung parasites in humans and dogs. The pharmacokinetics of FBZ parent drug and its metabolites in dogs were characterized by McKellar et al. (1990, 1993, who detected FBZ, its active sulphoxide (OFZ) and inactive sulphone (FBZSO 2 ) metabolites in plasma for 48 h after administration of a single oral dose of 20 mg/kg (Fig.…”
Section: Benzimidazole Compoundsmentioning
confidence: 99%
“…This results in exposure of the parasites to the FBZ moiety which has greater potency than OFZ, and thus activity against the tissue arrested larvae and other immature parasite stages (Fig. 4; McKellar et al. , 1990).…”
Section: Benzimidazole Compoundsmentioning
confidence: 99%